Comparing the pace of life of a city: Size and average temperature as predictors - Permatasari, Intan; Baswara, Boma; Adira, Nesya (Faculty of Psychology, Universitas Negeri Yogyakarta, 2022)
Pace of life has been found to be associated with various life outcomes such as mental health and well-being to information distribution and economic development. Every city has a different pace of life due to its specific characteristics. Across two studies, we examined the role of temperature and number of populations (city size) as the predictors of pace of life. In the first study, we compared Bandung and Jakarta and in the second study, we compared Jakarta and Depok. Each pace of life index was generated by mean scores of walking speed, working speed and clock accuracy. Through field observation in each city's Central Business District, we found that based on temperature, Jakarta has higher means of walking speed (M=15.3) compared to Bandung (M=13.6), significantly with mean difference 1.71 (t(158)=5.32, p<.001, d=0.841). Jakarta is also significantly higher on the working speed indicator (M=25.7) compared to Bandung (M=17.5) with mean difference 8.22 (t(18)=2.49, p=.011). In the second study, we found that Jakarta has significantly lower means of walking speed (M=14.3) compared to Depok (M=17.9) with mean difference 3.54, t(158)=11.058, p<.001. Similarly, Jakarta also has lower means of working speed (M=18.58) and clock accuracy (M=1.33) compared to Depok (M working speed=19.9, M clock accuracy=3.67), although not significant. Overall, as predicted, based on temperature, the colder city Bandung has a faster pace of life compared to Jakarta. Jakarta also has a faster pace of life compared to Bandung, although significant only for its walking speed.